Association of emergency department albuterol dispensing with pediatric asthma revisits and readmissions. (28th May 2017) - Hall, A. Brad; Novotny, April; Bhisitkul, Donna M.; Melton, James; Regan, Tim; Leckie, Maureen
ABSTRACT: Introduction : Although pediatric asthma continues to be a highly studied disease, data to suggest clear strategies to decrease asthma related revisits or readmissions is lacking. The purpose of our study was to assess the effect of emergency department (ED) direct dispensing of beta-agonist metered dose inhalers on pediatric asthma ED revisit and readmission rates. Methods : We conducted a retrospective cohort study of pediatric patients discharged from the pediatric ED with a diagnosis of asthma. Our primary outcome measured the rate of asthma revisits to the ED or admissions to the hospital within 28 days. Logistic regression analysis was used to assess ED beta-agonist MDI dispensing and revisit and/or readmission as the outcome. Results : A total of 853 patients met eligibility for inclusion in the study, with 657 enrolled in the Baseline group and 196 enrolled in the ED-MDI group. The Baseline group experienced a revisit and readmission rate of 7.0% (46/657) versus 2.6% (5/196) in the ED-MDI group, (p = 0.026). ED direct dispensing of MDIs was found to be independently associated with a decreased risk of revisit or readmission (odds ratio 0.37; 95% confidence interval 0.14–0.95). Conclusions : In our study, ED direct dispensing of beta-agonist MDIs resulted in a reduction in 28-day revisit and readmission to the hospital. Further studies should be performed to evaluate the economic impact of reducing these revisits and readmissions against the costs of maintaining a dispensing program. Our findings may support modification of asthma programs to include dispensing MDIs from the emergency department.